The relationship between insulin resistance, metabolic syndrome and nonalcoholic fatty liver disease in non-obese non-diabetic Turkish individuals: A pilot study - Erkan, Gülbanu; Sayın, Irmak; Polat, Fatma Betül; Çorakçı, Ahmet; Ataç, Gökçe Kaan; Değertekin, Halil (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Nonalcoholic fatty liver disease is related to obesity, metabolic syndrome, and insulin resistance. Nonalcoholic fatty liver disease and metabolic syndrome may also be encountered in non-obese, non-diabetic individuals, and there are no published data about the prevalence of these conditions in non-obese, non-diabetic Turkish subjects. We aimed to determine the difference between non-obese, non-diabetic nonalcoholic fatty liver disease patients and healthy controls in terms of insulin resistance and metabolic syndrome in Turkish subjects. Materials and Methods: Non-obese, non-diabetic individuals (n=219) were enrolled. The cohort was divided into two groups according to presence of steatosis in ultrasonography: nonalcoholic fatty liver disease group (n=143) and healthy control group (n=76). Insulin resistance and metabolic syndrome were analyzed and compared between the two groups. Results: The prevalences of metabolic syndrome (32.2% vs. 5.3%, respectively; p<0.001) and insulin resistance (46.2% vs. 9.2%, respectively; p<0.001) were significantly higher in the nonalcoholic fatty liver disease group. According to multiple logistic regression analysis, age (odds ratio 1.534; p=0.0032), insulin resistance (odds ratio 1.074; p<0.001), and serum ALT levels (odds ratio 1.102; p<0.001) were independently associated with nonalcoholic fatty liver disease. Conclusion: Insulin resistance and metabolic syndrome are not rare in non-obese, non-diabetic Turkish subjects with nonalcoholic fatty liver disease. Ultrasonographically detected fatty liver was independently associated with insulin resistance, irrespective of the presence of metabolic syndrome.